2022
DOI: 10.1002/ange.202113302
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Vinyl Random Copolymers via Photocontrolled Radical Ring‐Opening Cascade Copolymerization**

Abstract: Degradable vinyl polymers by radical ring-opening polymerization are promising solutions to the challenges caused by non-degradable vinyl plastics. However, achieving even distributions of labile functional groups in the backbone of degradable vinyl polymers remains challenging. Herein, we report a photocatalytic approach to degradable vinyl random copolymers via radical ring-opening cascade copolymerization (rROCCP). The rROCCP of macrocyclic allylic sulfones and acrylates or acrylamides mediated by visible l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 74 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…It is important that the reactive triggers for cleavage are consistently incorporated throughout the backbone to prevent the formation of large nondegradable fragments. [29] Thus, in our system, the consistent incorporation of MAA triggers into polymer chains was integral for attaining optimal degradation. Promisingly, the pseudo-first-order kinetics plot of MMA and MAA, during copolymerization to synthesize P(MMA-co-MAA) 10% , confirmed that the two monomers reacted at nearly identical rates (Figure S4).…”
Section: Post-polymerization Modification Strategies Have Advancedmentioning
confidence: 92%
See 3 more Smart Citations
“…It is important that the reactive triggers for cleavage are consistently incorporated throughout the backbone to prevent the formation of large nondegradable fragments. [29] Thus, in our system, the consistent incorporation of MAA triggers into polymer chains was integral for attaining optimal degradation. Promisingly, the pseudo-first-order kinetics plot of MMA and MAA, during copolymerization to synthesize P(MMA-co-MAA) 10% , confirmed that the two monomers reacted at nearly identical rates (Figure S4).…”
Section: Post-polymerization Modification Strategies Have Advancedmentioning
confidence: 92%
“…This has been performed by cleaving C−S linkages in the end groups of polymers synthesized by RAFT or terminal C−Cl bonds to form chain‐end radicals that can then unzip the polymer backbone [27] . An alternative method that does not rely on chain‐end triggers is the incorporation of hydrolysable groups into the polymer chain through radical ring‐opening copolymerization with thionolactones, macrocyclic allylic sulfones, or cyclic ketene acetals [28, 29] . Additionally, comonomers that can generate carbon‐centered radicals and subsequently lead to cleavage of adjacent C−C bonds may be integrated in poly(meth)acrylate backbones to achieve degradation [12, 30] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, copolymerization of heteroatom‐containing cyclic monomers with common vinyl monomers, by which labile carbon‐heteroatom bonds can be introduced via ring opening of the cyclic structures, is one of the most efficient methods [23–26] . Various cyclic compounds, which are copolymerizable via ring‐opening reactions, have been developed to date and include cyclic ketene acetals, [27–40] thionolactones, [41–47] and cyclic allylic sulfur compounds [48–52] for radical polymerization as well as oxiranes, [53, 54] cyclic acetals, [55, 56] hemiacetal esters, [57] and 1,3‐dioxa‐2‐silacycloalkanes [58] for cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%